Difusão tecnológica no ensino de línguas: o uso de computadores portáteis nas aulas de língua portuguesa sob a ótica da complexidade - Adriana Gouvea Dutra Teixeira (2012)
The integration of technology in the educational context is one of the pillars of contemporary Brazilian educational governmental policies, in particular, ProInfo and PROUCA. Both programs are responsible for bringing the computer inside the school environment. This research aims to present how Portuguese-speaking teachers adopt guidelines of these policies and how they incorporate the use of laptops in the classroom. This study subscribes to the paradigm of complexity by applying a systemic approach to context observation that prioritizes the interaction of agents. Also, by acknowledging the Model of Diffusion of Innovation, as defined by Rogers (2003), as a model that shows the diffusion of innovation as a multifaceted factor. The methodology of this study is qualitative and was developed in two stages. In the first stage, I present the model of diffusion of innovations by Rogers (2003) applied to the Brazilian federal government programs ProInfo and PROUCA. The facilitators that are involved with both programs answered surveys to indicate how the programs guidelines are communicated among the various agents until they reach the schools. In the second stage, the objective was to observe teachers in the classroom. Therefore, the main focus was given to PROUCA, in order to analyze the perceptions of participants students and teachers of UCA Total, a program that aims to give laptops to all public schools in a chosen city. At this stage, I collected narratives and testimonies from students and teachers, and analyzed them according to the principles of the theory of Lieblich et al. (1998) on narrative research. The analysis was conducted holistically, in the light of the proposed theories. The results show how the technology has been incorporated into the Portuguese Language classes and the changes that arise from the interaction with the laptop. Furthermore, the data reflects the difficulties and fears faced by teachers in the implementation of the Project UCA in the city of Tiradentes, Minas Gerais, Brazil.